A novel individual‐cell‐based mathematical model based on multicellular tumour spheroids for evaluating doxorubicin‐related delivery in avascular regions. (30th July 2017) - Liu, Jiali; Yan, Fangrong; Chen, Hongzhu; Wang, Wenjie; Liu, Wenyue; Hao, Kun; Wang, Guangji; Zhou, Fang; Zhang, Jingwei
Abstract : Background and Purpose: Effective drug delivery in the avascular regions of tumours, which is crucial for the promising antitumour activity of doxorubicin‐related therapy, is governed by two inseparable processes: intercellular diffusion and intracellular retention. To accurately evaluate doxorubicin‐related delivery in the avascular regions, these two processes should be assessed together. Here we describe a new approach to such an assessment. Experimental Approach: An individual‐cell‐based mathematical model based on multicellular tumour spheroids was developed that describes the different intercellular diffusion and intracellular retention kinetics of doxorubicin in each cell layer. The different effects of a P‐glycoprotein inhibitor (LY335979) and a hypoxia inhibitor (YC‐1) were quantitatively evaluated and compared, in vitro (tumour spheroids) and in vivo (HepG2 tumours in mice). This approach was further tested by evaluating in these models, an experimental doxorubicin derivative, INNO 206, which is in Phase II clinical trials. Key Results: Inhomogeneous, hypoxia‐induced, P‐glycoprotein expression compromised active transport of doxorubicin in the central area, that is, far from the vasculature. LY335979 inhibited efflux due to P‐glycoprotein but limited levels of doxorubicin outside the inner cells, whereas YC‐1 co‐administration specifically increased doxorubicin accumulation in the inner cells without affecting the extracellular levels. INNO 206 exhibited a more effective distribution profile than doxorubicin. Conclusions and Implications: The individual‐cell‐based mathematical model accurately evaluated and predicted doxorubicin‐related delivery and regulation in the avascular regions of tumours. The described framework provides a mechanistic basis for the proper development of doxorubicin‐related drug co‐administration profiles and nanoparticle development and could avoid unnecessary clinical trials.